Distribution and ecology of genus Tricholoma (Tricholomataceae) in the Republic of Macedonia - Karadelev, Mitko; Rusevska, Katerina; Markova, Natalija (Macedonian Journal of Ecology and Environment, 2008)
This is the first publication on systematic research of the genus Tricholoma in the Republic of Macedonia. In previous studies, there have been 35 species of this genus identified in the Republic of Macedonia, of the 55 species found in Europe. The following 15 species are new for the mycobiota in the Republic of Macedonia: Tricholoma album, T. apium, T. basirubens, T. colossum, T. columbetа, T. populinum, T. pseudonictitans, T. sejunctum, T. stans, T. sulphurescens, T. tigrinum, T. ustale, T. ustaloides, T. vaccinum and T. viridifucatum. Detailed distribution of Tricholoma species in the Republic of Macedonia is presented in this paper as well as their affinity for different habitat types.